Wpływ użytkowania gleb na zawartość fosforu i potasu w glebach rdzawych = Influence of the cultivation of soils on the content of phosphorus and potassium in rusty soils - Wawrzyniak-Gramacka, Edyta; Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Paper presents the results of comparative studies of post agricultural rusty soils and forest soils adjoining to then as regards content of phosphorus and potassium. The two types of soils, independently of the cultivation type, were characterized by low level of marked elements. This behavior suggests the need for fertilization with P and K. Acidification and the quantity of organic carbon had an influence on the amount of phosphorus and potassium in those soils.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); fosfor; potas; gleby rdzawe; phosphorus; potassium; rusty soils